EFEKTIVITAS PEMERIKSAAN PAJAK DALAM UPAYA MENINGKATKAN PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA SURABAYA - Ali Muhdor (AKUNTANSI 45, 2021)
Tax is one of highest sources of state revenue. Qualitative research methods are methods based on the philosophy of postpositivism. The conclusions are as follows: 1. The tax audit carried out by the audit team is in accordance with the guidelines in the Regulation of the Minister of Finance. 2. The results of the calculation of the effectiveness level, in 2015-2018 are included in the effective criteria with a percentage of 100%, and in 2019 they are included in the effective criteria with a percentage of 91.1%.3. The results of the calculation of the level of effectiveness based on the realization of tax audit receipts in 2015-2019 based on targets and the realization of ineffective audits, 4. Factors that affect tax audits include unclear taxpayer addresses, different attitudes of taxpayers, sense of responsibility responsibility of the examiner, human resources, adequate office facilities, good communication, and support from the leadership and good cooperation between leaders.